Morphological Differences of Knee Extensor Muscles Between Women With and Without Lateral Patellar Compression Syndrome - Seyyed Hossein Hosseini; Saeed Ghobadi Nezhad (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims: The morphology of knee joint extensor muscles including vastus medialis (VM) and vastus lateralis (VL), is one of the important and effective factors in lateral patellar compression syndrome (LPCS). This study aims to examine the morphological differences of these knee extensor muscles between women with and without LPCS.Methods: In this causal-comparative study, 15 women with LPCS aged 18-30 years and 15 women without LPCS as controls participated who were selected by a convenience sampling methhod. For muscle imaging, the anteromedial (VM) and anterolateral (VL) thigh distal ends were scanned by using a two-dimensional digital ultrasound device (SonoSite Co., USA). The muscles' cross-sectional area at the patellar base was measured in square centimeters and the muscle-fiber pennation angles of these muscles was measured in degree. Independent t-test was used to compare the variables between the two groups. The significance level was set at 0.05.Results: The cross-sectional area of VM in the control group was significantly higher than in the LPCS group (P=0.001), while the cross sectional area of VL was not significantly different between the two groups (P>0.05). The muscle-fiber pennation angle of VM in the LPCS group was significantly lower than in the control group (P=0.016), while the muscle-fiber pennation angles of VL in the LPCS group was significantly higher than in the control group (P=0.021).Conclusion: The morphology of VM and VL in women with LPCS symptoms shows a significant muscle imbalance that can change the patella position from normal to a more lateral position and increase the contact between the lateral facet of the patella and the lateral femoral condyle, resulting in increased pressure on this area and eventually knee pain.Muscle morphology, Cross-sectional area, Muscle-fiber pennation angle, Lateral patellar compression syndrome, Knee extensors